Bridging minds and markets: The South African experience - Dewar, Neil; Shippey, Karen (Acta Structilia, 2001)
At present an historical conjuncture of separate and essential unrelated developments concerning environmental management are occurring in South Africa. These include the issues of standards assurance, certification of environmental practitioners and the development of curricula for a professional science degree at tertiary level. All these are occurring in the context of a rapidly expanding job market into which graduates with widely varying educational standards and practical competence are entering. This article reports on a survey of professionals in environmental impact assessment and environmental management in South Africa that elicited opinions on the quality and appropriateness of professional training. It seeks to inform debate concerning these topics and to highlight limitations in the structure and content of contemporary education. It is argued that there is little standardization across curricula and that the core competencies as recognised by professionals are frequently being neglected.